RESILIENSI PADA PENYANDANG TUNA DAKSA NON BAWAAN - Imelda Pratiwi; Hartosujono Hartosujono (JURNAL SPIRITS, 2014)
ABSTRACTÂ Physical changes are caused by accident are very shaken soul, especially when they get a negative judgment from others. This mental turmoil often lead to negative self image. Person with disabilities experience pressure use to think in accurate way. The purpose of this study was to determine the extent of resilience in physically disabled for life and rise from adversity. Subjects of this study were four people with non congenital deformities, with the characteristics of two men and two women were self-employed workers aged around 30-45 years who have been through a period of rehabilitation in YAKKUM. Approach of this study was qualitative methods using interviews and observations. Analysis of data technique using the reduction of data, data display, and conclusion triangulation and verification. Elaborate the research showed that four subjects had good resilience capability. It can be seen through the subject's ability to control emotions, impulse control ability, optimism, ability to analyze problems well, empathy, self-efficacy and achievement. Supporting factors also affect the ability of the four subjects is resilience of individual factors, family factors and community factors. Â Keywords: Physically disabled, Resilience, Self-Efficacy, impulseÂ